Non-destructive, in-situ, fast identification of adverse geology in tunnels based on anomalies analysis of element content. (December 2021) - Xu, Zhenhao; Liu, Fumin; Lin, Peng; Shao, Ruiqi; Shi, Xuesong
Highlights: A non-destructive, in-situ, fast identification method of adverse geology is proposed. The anomalies analysis of element content is applied to identify adverse geology. The occurrence of adverse geology can be identified in time. Geological qualitative analysis in tunnels is improved to quantitative analysis. The identification method was successfully applied and verified in a tunnel. Abstract: A non-destructive, in-situ, fast identification method of adverse geology in tunnels is proposed based on element content anomaly analysis. The element contents of the surrounding rocks were analyzed using a portable X-ray fluorescence (XRF) spectrometer. The major elements in the rocks were selected as the indexes for identifying the adverse geology. The major element contents of the background zones were used to establish reference samples. Either the mean standard deviation method or the cumulative frequency method was used to calculate the thresholds of the reference samples based on the normality test. The thresholds of the reference samples were used to judge the element content anomalies in the targeted zones. The element content anomaly characteristics were used to identify the adverse geology, such as faults and alteration zones. The proposed method was successfully applied to identify a fault in a granite tunnel. Thus, this non-destructive, in-situ, fast identification method was verified for use in practical engineering projects, and it can also be used in similar geological, mining, and underground projects.